The Streptomyces coelicolor Small ORF trpM Stimulates Growth and Morphological Development and Exerts Opposite Effects on Actinorhodin and Calcium-Dependent Antibiotic Production - Vassallo, Alberto; Palazzotto, Emilia; Renzone, Giovanni; Botta, Luigi; Faddetta, Teresa; Scaloni, Andrea; Puglia, Anna Maria; Gallo, Giuseppe (Frontiers in Microbiology, 2020)
In actinomycetes, antibiotic production is often associated with a morpho-physiological differentiation program that is regulated by complex molecular and metabolic networks. Many aspects of these regulatory circuits have been already elucidated and many others still deserve further investigations. In this regard, the possible role of many small open reading frames (smORFs) in actinomycete morpho-physiological differentiation is still elusive. In Streptomyces coelicolor, inactivation of the smORF trpM (SCO2038) – whose product modulates L-tryptophan biosynthesis – impairs production of antibiotics and morphological differentiation. Indeed, it was demonstrated that TrpM is able to interact with PepA (SCO2179), a putative cytosol aminopeptidase playing a key role in antibiotic production and sporulation. In this work, a S. coelicolor trpM knock-in (Sco-trpMKI) mutant strain was generated by cloning trpM into overexpressing vector to further investigate the role of trpM in actinomycete growth and morpho-physiological differentiation. Results highlighted that trpM: (i) stimulates growth and actinorhodin (ACT) production; (ii) decreases calcium-dependent antibiotic (CDA) production; (iii) has no effect on undecylprodigiosin production. Metabolic pathways influenced by trpM knock-in were investigated by combining two-difference in gel electrophoresis/nanoliquid chromatography coupled to electrospray linear ion trap tandem mass spectrometry (2D-DIGE/nanoLC-ESI-LIT-MS/MS) and by LC-ESI-MS/MS procedures, respectively. These analyses demonstrated that over-expression of trpM causes an over-representation of factors involved in protein synthesis and nucleotide metabolism as well as a down-representation of proteins involved in central carbon and amino acid metabolism. At the metabolic level, this corresponded to a differential accumulation pattern of different amino acids – including aromatic ones but tryptophan – and central carbon intermediates. PepA was also down-represented in Sco-trpMKI. The latter was produced as recombinant His-tagged protein and was originally proven having the predicted aminopeptidase activity. Altogether, these results highlight the stimulatory effect of trpM in S. coelicolor growth and ACT biosynthesis, which are elicited through the modulation of various metabolic pathways and PepA representation, further confirming the complexity of regulatory networks that control antibiotic production in actinomycetes.